Dual decline in gait speed and cognition is associated with future dementia: evidence for a phenotype - Montero-Odasso, Manuel (Age Ageing, 2020)
BACKGROUND: concurrent declines in gait speed and cognition have been associated with future dementia. However, the clinical profile of ‘dual decliners’, those with concomitant decline in both gait speed and cognition, has not been yet described. We aimed to describe the phenotype and the risk for incident dementia of those who present with dual decline in comparison with non-dual decliners. METHODS: prospective cohort of community-dwelling older adults free of dementia at baseline. We evaluated participants’ gait speed, cognition, medical status, functionality, incidence of adverse events and dementia, biannually over 7 years. Gait speed was assessed with a 6-m electronic walkway and global cognition using the MoCA test. We compared characteristics between dual decliners and non-dual decliners using t-test, chi-square and hierarchical regression models. We estimated incident dementia using Cox models. RESULTS: among 144 participants (mean age 74.23 ± 6.72 years, 54% women), 17% progressed to dementia. Dual decliners had a 3-fold risk (HR: 3.12, 95%CI: 1.23–7.93, P = 0.017) of progression to dementia compared with non-dual decliners. Dual decliners were significantly older with a higher prevalence of hypertension and dyslipidemia (P = 0.002). Hierarchical regression models show that age and sex alone explained 3% of the variation in the dual decliners group. Adding hypertension and dyslipidemia increased the explained variation by 8 and 10%, respectively. The risk of becoming a dual decliner was 4-fold higher if hypertension was present. CONCLUSION: older adults with a concurrent decline in gait speed and cognition represent a group at the highest risk of progression to dementia. Older adults with dual decline have a distinct phenotype with a higher prevalence of hypertension, a treatable condition.